SOCIALIZATION OF MOTIVATION AND DISCIPLINE IN ACCOUNTING TO ENHANCE PROFESSIONAL AWARENESS AMONG STUDENTS OF SMKN 3 KARAWANG - Nanu Hasanuh; Sri Suartini; Achmad Nawawi; Nesti Hapsari (PT. Jurnal Center Indonesia Publisher, 2025)
Community Service (Pengabdian Kepada Masyarakat-PKM) is a fundamental implementation of the Tri Dharma of Higher Education. This activity aims to address the need for strong motivation and discipline among Vocational High School (Sekolah Menengah Kejuruan - SMK) students, particularly those majoring in Accounting, as crucial preparation for entering the workforce or continuing their education. This PKM was conducted through an interactive socialization session involving 12th-grade Accounting students at SMKN 3 Karawang, using presentation, discussion, and Question & Answer methods. The results indicate a significant increase in participants' enthusiasm and understanding of accounting principles, career prospects, and professional ethics. Furthermore, the activity successfully fostered a collaborative partnership between the university and the school, while also enhancing the social skills of the implementing student team. In conclusion, this socialization proved to be an effective medium for knowledge and motivation transfer. It is recommended that similar initiatives be developed sustainably and expanded in scope to maximize their positive impact.